Does Domestic Credit of the Banking Sector Promote Economic Growth? Evidence from Bangladesh - Al Mamun, Mohammad Salim; Ariffin, Muhammad Irwan; Hamid, Zarinah (UUM Press, 2018)
The objective of the study is to investigate the relationship between domestic credit and economic growth for Bangladesh economy. The paper attempts to link between financial development and economic growth in answering a question whether the credit channeling through banking system goes to productive activities that bring economic growth in a country. Sample data was taken for the period 1975-2016 for year-wise trend analysis while econometric specification applies autoregressive distributed lag (ARDL) model and uses quarterly data for the period 1980Q1-2016Q2. The Bangladesh economy experienced structural changes initiated at the beginning of the 1990s that are addressed in the specification by dividing the full sample period into two sub-samples (19980Q1-1990Q4 and 1991Q1-2016Q2). Overall, the paper finds that an increase in real domestic credit impacts positively on real GDP and the impact is found to be statistically highly significant. On the other hand, the results indicate that an increase in real lending rates decreases real GDP. However, this result is not statistically significant. Respective policy-makers need to initiate appropriate market-based policy rates that can impact GDP growth through domestic credit channel since this paper finds that domestic credit effectively enhances GDP growth.